The Role Of Smart Leadership Dimensions In Crisis Management- A study For Opinions Of Sample Of Administrative Leaderships In A number Of Humanities Colleges At The University Of Mosul - Al-Jameel, Reem Saad (Journal of Economics and Administrative Sciences, 2022)
This research aims at answering many questions raised by the research problem concerning the view of the organizations under consideration for the concept of smart leadership and its most important dimensions, as well as the view of crisis management and its concept and most important methods through research objectives that define and clarify the smart leadership with its dimensions and methods of crisis management. For the purpose of reaching the results of the research and testing the assumptions about the relationship between smart leadership and methods of crisis management, the researcher adopted a questionnaire, designed especially to be a criterion for the research, as the main tool for data collection. The results of the research sample, which consisted of (44) respondents from administrative leaders working in a number of humanities colleges at the University of Mosul, were analyzed, and important results were reached related to the existence of crisis management methods at the administrative leaders which work through smart leadership in the organization under consideration. The relation between the two variables was one of a strong correlation and the effect was significant between these two variables. The results confirmed the hypothesis of the research, and explanation of the role played by smart leadership in terms of its dimensions in crisis management in the researched field